Evaluation of the relationship between the minimum inhibitory concentration of ceftiofur and third-generation cephalosporins in Escherichia coli isolates from food-producing animals. (September 2017) - Hiki, Mototaka; Shimizu, Yasuhito; Kawanishi, Michiko; Ozawa, Manao; Abo, Hitoshi; Kojima, Akemi; Koike, Ryoji; Suzuki, Satowa; Asai, Tetsuo; Hamamoto, Shuichi
To enable future comparison of the antimicrobial susceptibility data between bacteria obtained from animals and humans, it is necessary to compare the relationships between minimum inhibitory concentrations (MICs) of veterinary and human medicine. We evaluated the relationship between the MIC of ceftiofur (CTF) and the MICs of other third-generation cephalosporins (TGCs): cefotaxime (CTX), cefpodoxime (CPDX), and ceftazidime (CAZ), determined by the broth microdilution method using 118 cefazolin-resistant Escherichia coli isolates from food-producing animals. Using the Clinical and Laboratory Standards Institute criteria, very major classification errors were observed only in CAZ (17.8%, 21 of 118); major and minor errors were observed in all TGCs (CTX: 0.8% [1 of 118] and 9.3% [11 of 118]; CPDX: 9.3% [11 of 118] and 6.8% [8 of 118]; CAZ: 2.5% [3 of 118] and 9.3% [11 of 118], respectively). The Spearman correlation coefficients between the MICs of CTF and CTX, CPDX, and CAZ were 0.765, 0.731, and 0.306, respectively. The sensitivity and specificity values were 100.0% and 81.8% for CTX, 99.0% and 27.3% for CPDX, and 76.0% and 86.4% for CAZ compared with CTF. The C-statistic was 0.978 for CTF and CTX, 0.953 for CPDX, and 0.798 for CAZ. For the TGCs evaluated in our study, testing for CTX susceptibility results showed the highest correlation with the results given when testing for CTF susceptibility.